(untitled) (Journal of Asian Development Studies, 2025)
This study measures the consequences of Governance and financial development (FD), Economic activity and energy on the environmental quality of five ASEAN nations specifically Malaysia, Indonesia, Thailand, Vietnam, and the Philippines. By using the panel data covering the period from 2000 to 2018 the EKC hypothesis has been examined. The outcomes of the study exhibit that governance and FD have a substantial positive impact on the environmental quality. Whereas, the economic growth and energy are discovered to be havoc for the environmental quality. Based on the empirical outcomes, it is suggested that the ASEAN countries must improve the governance and financial development to have an improved environmental quality. Moreover, economic growth must be achieved by using the non renewable energy sources.